Assessment of Timoshenko Beam Models for Vibrational Behavior of Single-Walled Carbon Nanotubes Using Molecular Dynamics (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we study the flexural vibration behavior ofsingle-walled carbon nanotubes (SWCNTs) for the assessment ofTimoshenko beam models. Extensive molecular dynamics (MD)simulations based on second-generation reactive empirical bond-order(REBO) potential and Timoshenko beam modeling are performed todetermine the vibration frequencies for SWCNTs with variouslength-to-diameter ratios, boundary conditions, chiral angles andinitial strain. The effectiveness of the local and nonlocalTimoshenko beam models in the vibration analysis is assessed usingthe vibration frequencies of MD simulations as the benchmark. It isshown herein that the Timoshenko beam models with properly chosenparameters are applicable for the vibration analysis of SWCNTs. Thesimulation results show that the fundamental frequencies areindependent of the chiral angles, but the chirality has anappreciable effect on higher vibration frequencies. The SWCNTs isvery sensitive to the initial strain even if the strain is extremelysmall.